New advances in the treatment of generalized anxiety disorder: the multimodal antidepressant vortioxetine. (3rd May 2016) - Orsolini, Laura; Tomasetti, Carmine; Valchera, Alessandro; Iasevoli, Felice; Buonaguro, Elisabetta Filomena; Vellante, Federica; Fornaro, Michele; Fiengo, Annastasia; Mazza, Monica; Vecchiotti, Roberta; Perna, Giampaolo; de Bartolomeis, Andrea; et al.
ABSTRACT: Generalized Anxiety Disorder (GAD) is a persistent condition characterized by chronic anxiety, exaggerated worry and tension, mainly comorbid with Major Depressive Disorder (MDD). Currently, selective serotonin reuptake inhibitors and serotonin-norepinephrine reuptake inhibitors are recommended as first-line treatment of GAD. However, some patients may not respond to the treatment or discontinue due to adverse effects. Vortioxetine (VRX) is a multimodal antidepressant with a unique mechanism of action, by acting as 5-HT3A, 5-HT1D and 5-HT7 receptor antagonist, partial agonist at the 5-HT1A and 5-HT1B receptors and inhibitor at the 5-HT transporter. Preliminary clinical trials showed contrasting findings in terms of improvement of the anxiety symptomatology and/or cognitive impairment. Here, we aim to systematically review the evidence currently available on the efficacy, safety and tolerability of VRX in the treatment of GAD. The generalizability of results on the efficacy of VRX in patients with anxiety symptomatology and GAD is limited due to few and contrasting RCTs so far available. Only two studies, of which one prevention relapse trial, reported a significant improvement in anxiety symptomatology compared to three with negative findings.